Prisons and community corrections: critical issues and emerging controversies - Birch, Philip; Sicard, Louise A. (Routledge innovations in corrections, 2021)
"This edited collection brings together leading international academics and researchers to provide a comprehensive body of literature that informs the future of prison and wider corrective services training, education, research, policy and practice. This volume addresses a range of 21st century issues faced by modern corrective services including, prison overcrowding, young and ageing offenders, mental health, sexual assault in corrective facilities, trans communities in corrective services and radicalisation of offenders within corrective services. Taking a multi-disciplinary approach and drawing together theoretical and practice debates, the book comprehensively considers current challenges and future trajectories for corrective systems, the people within them and service delivery. This volume will also be a welcomed resource for academics and researchers who have an interest in prisons, corrective services practice and broader criminal justice issues. It will also be of interest to those who want to join corrective services, those who are currently training to become personnel in corrective services and related allied professions, and those who are currently working in the field"--